2005
DOI: 10.1159/000087672
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein in Lymphocytic Pleural Effusions: A Diagnostic Aid in Tuberculous Pleuritis

Abstract: Background:C-reactive protein (CRP) pleural fluid levels have been found to be higher in tuberculosis and parapneumonic effusions than in other causes of pleural effusion. Objective:The aim of this study was to analyze whether CRP (a simple and inexpensive test) may be a diagnostic aid for tuberculosis in lymphocytic pleural effusions. Methods:One hundred and forty-four patients with a lymphocytic pleural effusion (more than 50% lymphocytes in the differential white blood cell count) were included. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
3
11
0
1
Order By: Relevance
“…This ¢nding could be explained by increased local production of CRP as a result of granuloma formation 35 and as a defence mechanism against the tubercle bacilli. Our results are concordant with other authors 4,36,37 who found a signi¢cant increase in pleural £uid CRP and suggested the use of CRP as an indication of tuberculous e¡usion. Moreover, in the current study, ROC curve analysis has shown that CRP and OPN are more sensitive markers for tuberculous rather than malignant e¡usion and CRP outperformed OPN as a marker for tuberculous e¡usion.…”
Section: Discussionsupporting
confidence: 93%
“…This ¢nding could be explained by increased local production of CRP as a result of granuloma formation 35 and as a defence mechanism against the tubercle bacilli. Our results are concordant with other authors 4,36,37 who found a signi¢cant increase in pleural £uid CRP and suggested the use of CRP as an indication of tuberculous e¡usion. Moreover, in the current study, ROC curve analysis has shown that CRP and OPN are more sensitive markers for tuberculous rather than malignant e¡usion and CRP outperformed OPN as a marker for tuberculous e¡usion.…”
Section: Discussionsupporting
confidence: 93%
“…We showed that a pleural fluid CRP level .80 mg?L -1 argues for the presence of a PPE (LR+ 7.4), whereas CRP levels ,20 mg?L -1 are a strong indicator against an infectious pleural effusion, whether of bacterial or mycobacterial nature (LR-0.22). Indeed, a number of studies provide support for the use of CRP as a diagnostic aid in tuberculous pleuritis; low pleural CRP levels (,30 mg?L -1 ) make this diagnosis unlikely while being more indicative of a malignancy in patients with exudates [8][9][10]. In addition, our findings complement the scarce previous literature on the application of CRP for identifying CPPE [11,12].…”
Section: Discriminating Ppe From Other Aetiologiessupporting
confidence: 70%
“…Invasive interventions such as closed pleural biopsy or thoracoscopy are often needed to confirm the diagnosis. Surrogate pleural fluid markers such as adenosine deaminase (ADA) and interferon (IFN)-γ have been proposed as an alternative [4, 5]. ADA determination by a technically simple colorimetric measurement has a mean sensitivity of 92% (range 56–100) and a mean specificity of 89% (range 55–100) [6].…”
Section: Introductionmentioning
confidence: 99%